Influence of glycemic control on fetal lung maturity in gestations affected by diabetes or mild hyperglycemia - De Luca, Ana Karina Cristiuma [UNESP]; Nakazawa, Cristiane Yoshie [UNESP]; Azevedo, Beatriz Camargo [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Costa, Roberto Antonio de Araújo [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP] (Taylor & Francis As, 2009)
Objective. To evaluate the influence of glycemic control on fetal lung maturity in pregnancies affected by diabetes or mild hyperglycemia. Design. Cross-sectional study. Setting. Level III maternity center. Population. A total of 187 pregnant women were submitted to routine amniocentesis for the assessment of fetal lung maturity up to 72 hours before delivery. Methods. Fetal lung maturity thresholds were: Clements-positive at a dilution of 0.5; OD(650) nm >= 0.15; and lamellar body count (LBC) >= 32,000/mu l. The relation of test results with adequate (<= 6.7 mmol/l) or poor (> 6.7 mmol/l) glycemic mean (GM) at term and at preterm was evaluated. Main outcome measure. Delay in fetal lung maturity when glycemic control was poor. Results. Glycemic control was adequate in 146 (78.1%) women. Clements maturity rates were higher at term (91.9%) than at preterm (64.7%) when GM <= 6.7 mmol/l (p < 0.001), but not when control was inadequate. LBC median was higher at term (99.0; 62.0-154.0) than at preterm (66.5; 40.5-108.25) (p = 0.009) when GM <= 6.7 mmol/l, while GM > 6.7 mmol/l did not lead to any difference between these rates at term or preterm. When glycemic control was adequate, OD(650) nm medians at term and at preterm were similar. However, when GM > 6.7 mmol/l, OD(650) nm median at term (0.29; 0.22-0.40) was higher than that observed at preterm (0.15; 0.12-0.18) (p < 0.001). Conclusions. Our results suggest that in term pregnancies routine amniocentesis for the assessment of fetal lung maturity should be abandoned. In preterm pregnancies, or when glycemic control is inadequate it is recommended.
Keywords: Fetal lung maturity; diabetes in pregnancy; amniocentesis